• Преобразуйте выражение:
    [tex](1 + \frac{3x + {x}^{2} }{x + 3} ) \div ( \frac{1}{x + 1} - \frac{x}{1 + 2x + {x}^{2} } )[/tex]

Ответы 1

  • Ответ:

    Объяснение:

    1. 1+(3x+x²)/(x+3)=1+(x*(x+3)/(x+3))=1+x=x+1.

    2. (1/(x+1))-x/(1+2x+x²)=(1/(x+1))-x/(x+1)²=(x+1-x)/(x+1)²=1/(x+1)².

    3. (x+1)÷1/(x+1)²=(x+1)*(x+1)²=(x+1)³.

  • Добавить свой ответ

Еще вопросы

Войти через Google

или

Забыли пароль?

У меня нет аккаунта, я хочу Зарегистрироваться

How much to ban the user?
1 hour 1 day 100 years